2023
DOI: 10.1037/sgd0000627
|View full text |Cite
|
Sign up to set email alerts
|

Young Black trans and gender-diverse activists' well-being among anti-Black racism and cissexism during the COVID-19 pandemic.

Abstract: Research has documented the negative mental health outcomes that anti-Black racism and cissexism, respectively, have had on Black and trans and gender-diverse (TGD) people during the COVID-19 pandemic. This research, however, has yet to explore the intersectional experiences of Black TGD young adults. Additionally, research has found that activists are often exposed to violence and discrimination. In this study, we aimed to understand how the intersection of anti-Black racism and cissexism has impacted young B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Importantly, trans identities may also intersect with other marginalized identities, magnifying both the barriers to health care access and the potential for health care biases. Black trans and gender‐queer people have multiple obstacles in health care, from doctors’ racism and transphobia to being unable to connect with a support group of their gender (Sostre et al., 2023).…”
Section: Covid‐19 and Health Care Inequitiesmentioning
confidence: 99%
“…Importantly, trans identities may also intersect with other marginalized identities, magnifying both the barriers to health care access and the potential for health care biases. Black trans and gender‐queer people have multiple obstacles in health care, from doctors’ racism and transphobia to being unable to connect with a support group of their gender (Sostre et al., 2023).…”
Section: Covid‐19 and Health Care Inequitiesmentioning
confidence: 99%
“…Due to the depth of these interviews and the impact activism and activism spaces have on this community, the authors found it important to write one manuscript specifically focusing on Black TGD people's experiences in activism and its impact. A previous manuscript focusing specifically on how the experiences of Black TGD young people during the COVID-19 pandemic with anti-Black and trans-specific violence impacted their well-being, including forms of coping, is currently in press (see Sostre et al, 2023). The previous manuscript explores and focuses on participant's broad experiences with violence during the COVID-19 pandemic, whereas the current manuscript explores participant's experiences with activism more broadly.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, researchers show that young TGD individuals experience disproportionately high rates of depression, suicidal ideation, and suicide attempts (Connolly et al, 2016). Although there is paucity of research about the impact of intersectional oppression on young Black TGD people's mental health, a recent study showed that experiencing or witnessing violence and discrimination not only impacted Black TGD young adults' mental health outcomes (e.g., symptoms of anxiety and depression), but also motivated them to engage in activism (Sostre et al, 2023).…”
Section: Anti-black Racism and Cissexismmentioning
confidence: 99%